Hubungan motivasi perawat terhadap pelaksanaan discharge Planning di ruang rawat inap RSI Siti Rahmah Padang - Nopan, Nopan Saputra (Sahabat Publikasi Kuu, 2023)
Discharge planning is part of the nurse's job, if given incorrectly it can cause harm to the patient. Data from the Family Care Giver Alliance showed that the result of incorrect discharge planning was (40%), patients experienced more than 65 medication errors after leaving the hospital, and (18%) patients were discharged from the hospital. The results of observations at RSI Siti Rahmah on 6 (six) out of 10 (ten) patients discharge planning formats after discharge were not filled in completely and there was no signature of the nurse and patient or family. The incomplete discharge planning format is when the patient first enters the inpatient room, the nurse fills in and completes the discharge planning when the patient is leaving. The research objective was to determine the relationship between motivation with the implementation of discharge planning. The research design was a cross sectional study. This research was conducted in the inpatient room of RSI Siti Rahmah Padang. The population in the study were all nurses in the inpatient room as many as 40 people. Data processing through the editing, coding, entry, and cleaning stages. Univariate analysis and bivariate analysis used the chi square test with a confidence degree of 95% α = 0.05. The results showed that the completeness of discharge planning by nurses was not complete as much as 35.0%, poor motivation was 40.0%. There is a significant relationship between motivation (p = 0.000) with the implementation of discharge planning.